For the Promotion of Partnerships between CTA and ACP - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Highlight of the opening day of the meeting marked by the CTA Director, Dr Hansjörg Neun, welcome address stressing the partners' grain of salt in the Centres' strategic plan 2007-2010.